Morphological characteristics of asbestos in ground bulk mineral powders - Pier, Julie Warner (Frontiers in Geochemistry, 2025)
IntroductionDifferences exist in the morphological features of asbestos and the abilities of measuring tools over the spectrum of the particle size distribution in ground bulk mineral powders. Amphiboles and serpentine most often occur naturally without an asbestos component, although amphiboles typically produce elongate mineral particles when ground. For reasons of defining health risks, attempts to conclusively distinguish between asbestos and non-asbestos occurrences are warranted. Asbestiform morphological characteristics are more readily visible in the coarser size fraction of a ground mineral powder. Therefore, a procedure was developed to isolate and analyze the coarse size fraction of mineral mixtures for asbestos.MethodsThe morphological characteristics of asbestos spiked into ground mineral powders at 100 ppm and 500 ppm concentrations were evaluated. Three types of asbestos, Lone Pine tremolite, Health and Safety Laboratory (HSL) chrysotile, and short-fiber Calidria chrysotile, were spiked into a coarsely crushed talc matrix. Spiked samples were aggressively co-ground to simulate a milled mineral powder final product. The coarsest particles in the mixture were isolated using a wet-sieving technique and evaluated by scanning electron microscopy (SEM) and polarizing light microscopy (PLM). A production-scale ultrafine milled talc sample containing trace amounts of amphibole was also analyzed using the wet-sieve approach.ResultsAsbestos was readily detected by both SEM and PLM in the coarsest size fraction at these low concentrations, despite aggressive grinding. Classic morphological features of asbestos, such as occurrence in bundles and presence of long, thin fibers showing curvature, were observed for all types of asbestos by both SEM and PLM at both concentrations. There were no morphology differences between the 500 ppm and 100 ppm concentrations, although fewer particles were observed in the latter, as expected. Trace amounts of amphibole asbestos were detected in the production-scale ultrafine milled talc sample which showed classic asbestiform morphology even though the sample had been ground to a 1.5 μm median particle size.DiscussionResults show that the presence of asbestos can be confirmed in ground bulk mineral powders using this analysis approach and detection by SEM and/or PLM is limited only by the amount of material analyzed. This approach is opposite to types of asbestos analyses that concentrate on the finest particles (such as those performed by transmission electron microscopy (TEM)), which can sometimes be inconclusive. The production-scale ultrafine milled talc sample provided proof of concept for this approach. The techniques described can be used to accurately determine if a mineral product contains asbestos or an asbestos component.